2011
DOI: 10.1099/ijs.0.022954-0
|View full text |Cite
|
Sign up to set email alerts
|

Olsenella umbonata sp. nov., a microaerotolerant anaerobic lactic acid bacterium from the sheep rumen and pig jejunum, and emended descriptions of Olsenella, Olsenella uli and Olsenella profusa

Abstract: Olsenella umbonata sp. nov., a microaerotolerant anaerobic lactic acid bacterium from the sheep rumen and pig jejunum, and emended descriptions of Olsenella, Olsenella uli and Olsenella profusa Strain A2 is an anaerobic, variably Gram-stain-positive, non-spore-forming, small and irregularly rod-shaped bacterium from the ruminal fluid of a sheep that has been described informally as a representative of 'Olsenella (basonym Atopobium) oviles'. Three phenotypically similar bacterial strains (lac15, lac16 and lac31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
97
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 47 publications
7
97
0
3
Order By: Relevance
“…Another bacterium found to be associated with PC in this study and which is also associated with human caries is Olsenella spp; a small, rod‐shaped microaerotolerant (moderately obligate) anaerobic bacterium which can ferment carbohydrates, predominantly to lactic acid but also to formic and acetic acids. Olsenella spp, such as O. profusa are associated with human caries affecting dentine , as well as root (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…Another bacterium found to be associated with PC in this study and which is also associated with human caries is Olsenella spp; a small, rod‐shaped microaerotolerant (moderately obligate) anaerobic bacterium which can ferment carbohydrates, predominantly to lactic acid but also to formic and acetic acids. Olsenella spp, such as O. profusa are associated with human caries affecting dentine , as well as root (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…Two other bacterial phyla that were significantly more abundant in white water than in clear water sediments were the Actinobacteria (average 8.3%) and the Chloroflexi (average 5.3%). Species of the actinobacterial genus Olsenella are lactic acid bacteria isolated from animal guts or oral cavities (Kraatz et al ., ). However, Olsenella has also been detected in groundwater (Bowman et al ., ) and anaerobic digestors (Riviere et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Atopobium was proposed as a new genus derived from Lactobacillus and Streptococcus with the type strain Atopobium minutum in 1992 based on comparative sequence analyses [26]. A close relationship between Atopobium and Olsenella was shown in the bigeneric Olsenella - Atopobium branch of the family Coriobacteriaceae, class Actinobacteria [27], which might have caused misidentification in our first RDP pyrosequencing pipeline attempt. We confirmed that the RDP Classifier misclassified the V1–V2 region of the 16S rRNA gene of Atopobium sp.…”
Section: Discussionmentioning
confidence: 98%